Implementation of ICT-based Inquiry Learning Model for Enhancing Critical Thinking Skills in Mechanical Waves Characteristics - Yunita, Sari; Rusnayati, Heni; Liliawati, Winny (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
Critical thinking skills are essential in 21st century education. However, students’ critical thinking skills remain underdeveloped. To align with contemporary advancements, curricula now demand integration with 21st century skills, including critical thinking and technology. This study aims to investigate the implementation of ICT-based inquiry learning model for enhancing critical thinking skills in mechanical wave characteristics. This study employed a pre-experimental research method, utilizing a one-group pretest-posttest design. The participants consist of 34 eleventh-grade students from a high school in Bandung district, selected through convenience sampling. The instruments used were critical thinking skills test. The improvement of critical thinking skills was analyzed using N-Gain. The results showed that students’ critical thinking skills increased an average N-Gain value of 0.35 in a moderate category and there is a significant difference between the pretest and the posttest shown by the Wilcoxon signed rank test, which is p value < 0.05. Thus, the ICT-based inquiry learning model can enhance students’ critical thinking skills on mechanical wave characteristics.